2017
DOI: 10.1177/2153368717691800
|View full text |Cite
|
Sign up to set email alerts
|

Do Race and Ethnicity Matter? An Examination of Racial/Ethnic Differences in Perceptions of Procedural Justice and Recidivism Among Problem-Solving Court Clients

Abstract: Over the years, a distinct body of research has emerged that examines procedural justice in problem-solving courts. However, there is virtually no research to date on racial and ethnic differences in perceptions of procedural justice among problemsolving court clients. The present study seeks to understand the complexities of judicial procedural justice and race/ethnicity within problem-solving courts. Using a convenience sample of 132 clients from two problem-solving courts in a southern state, this study add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
(128 reference statements)
1
11
0
Order By: Relevance
“…This suggests that the court's structure, service delivery, resources, and staff may have created a therapeutically responsive setting that benefitted Black participants. Although similar findings have been generated from evaluations of other types of problem-solving courts (Atkin-Plunk & Armstrong, 2016;Atkin-Plunk, Peck, & Armstrong, 2019), this result may be an idiosyncratic feature of the current setting. Results must be interpreted with these court elements in mind and should not be generalized to or interpreted as being representative of all reentry courts.…”
Section: Discussionsupporting
confidence: 74%
“…This suggests that the court's structure, service delivery, resources, and staff may have created a therapeutically responsive setting that benefitted Black participants. Although similar findings have been generated from evaluations of other types of problem-solving courts (Atkin-Plunk & Armstrong, 2016;Atkin-Plunk, Peck, & Armstrong, 2019), this result may be an idiosyncratic feature of the current setting. Results must be interpreted with these court elements in mind and should not be generalized to or interpreted as being representative of all reentry courts.…”
Section: Discussionsupporting
confidence: 74%
“…Her strategies of using casual conversation, assigned readings, and essay responses as methods to encourage discussion, motivation, and influence led to more opportunity for rapport building. Her consistent references to shared cultural-historical identity with participants established a rapport that may lead to higher levels of trust and increased effectiveness of procedural justice outcomes (Atkin-Plunk et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, this research highlights the fact that shared racial identity with authority does play a role with perceptions of fair treatment and justice, especially in a court setting. For example, Atkin-Plunk et al (2019) find that black PSC participants have significantly lower perceptions of procedural justice, possibly due to the lack of diversity of courtroom staff. However, these studies do not have the data to explore how the processes of shared racial/ethnic identity influence program outcomes.…”
Section: Problem Solving Courts and Racial Outcomesmentioning
confidence: 97%
“…Prior scholarship has shown that police procedural justice was an antecedent of court procedural justice (Baker et al, 2015; Casper et al, 1988). While this distinction between police procedural justice and court procedural justice is important, it also reflects the interconnectedness of the criminal justice system (Atkin-Plunk et al, 2019). Casper et al (1988), for example, created a procedural justice index that combined 16 questions about lawyer procedural justice, prosecutor procedural justice, and judge procedural justice in their assessment of litigants’ satisfaction with the outcomes of their court cases.…”
Section: Review Of the Literaturementioning
confidence: 99%